2011
DOI: 10.1519/jsc.0b013e3181e4f7ba
|View full text |Cite
|
Sign up to set email alerts
|

Which Measure of Drop Jump Performance Best Predicts Sprinting Speed?

Abstract: The purpose of this study was to evaluate which measure of a drop jump (DJ) has the highest correlation with sprinting speed over 60 m. For use of comparison, maximal leg strengths in a front squat, countermovement jump, and squat jump were also assessed. The subjects in the study were all high-caliber female university rugby players. Subjects did DJs from 0.12, 0.24, 0.36, 0.48, 0.60, 0.72, and 0.84 m. Jump height and reactive strength index (RSI) were calculated at each drop height. Pearson correlations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 5 publications
3
42
0
1
Order By: Relevance
“…However, the results of the present study suggest that rebound height (VDJ) and jump distance and normalised jump distance (HDJ) provide stronger relationships to short-sprint performance than RSI from VDJ and HDJ. This substantiates previous research (Holm et al, 2008;Shalfawi, Sabbah, Kailani, Tønnessen, & Enoksen, 2011;Barr & Nolte, 2011) and might be due to the inferior reliability compared to other DJ measures (Stålbom et al, 2007). As contact time is one of the two components of RSI, the findings could also be attributed to ground contact times (HDJ and VDJ) having very small correlations (p > 0.05) to any sprint times (R ≤ -0.295, and R ≤ -0.103, respectively).…”
Section: Best Predictors Of Sprint Performance Over Each Time Splitsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the results of the present study suggest that rebound height (VDJ) and jump distance and normalised jump distance (HDJ) provide stronger relationships to short-sprint performance than RSI from VDJ and HDJ. This substantiates previous research (Holm et al, 2008;Shalfawi, Sabbah, Kailani, Tønnessen, & Enoksen, 2011;Barr & Nolte, 2011) and might be due to the inferior reliability compared to other DJ measures (Stålbom et al, 2007). As contact time is one of the two components of RSI, the findings could also be attributed to ground contact times (HDJ and VDJ) having very small correlations (p > 0.05) to any sprint times (R ≤ -0.295, and R ≤ -0.103, respectively).…”
Section: Best Predictors Of Sprint Performance Over Each Time Splitsupporting
confidence: 90%
“…It has been shown that contact times during VDJ are often above 250ms in moderately trained athletes (McCurdy et al 2010;Barr & Nolte, 2011;Ball & Zanetti, 2012;Dobbs, Gill, Smart & McGuigan, 2015). Thus, do not match sprinting ground contact times (Schmidtbleicher, 1992;Hunter et al, 2005;Coh & Tomazin, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Indices of strength, power, reactive strength and asymmetry have previously been highlighted as predictors of both linear (5,37) and multidirectional (16,29,38) sprint performance. Indeed, faster multidirectional speed performances, greater relative lower body strength, and higher magnitude plant foot kinetics have been observed in stronger versus weaker recreational team sports players (29).…”
Section: Introductionmentioning
confidence: 98%
“…Reactive strength has been previously described as a measure of an individual’s ability to change from an eccentric contraction to a concentric contraction (Young, 1995). It has been widely studied due to its association to sprint performance (Cronin and Hansen, 2005; Barr and Nolte, 2011), ability to monitor neuromuscular fatigue (Hamilton, 2009; Beattie and Flanagan, 2015) and ability to identify individual limb differences (Flanagan et al, 2008; Schiltz et al, 2009). …”
Section: Introductionmentioning
confidence: 99%